THE INFLUENCE OF CONSUMER BEHAVIOR ON PRODUCT PURCHASE DECISIONS THROUGH SHOPEE AMONG XYZ UNIVERSITY STUDENTS - Yusnaini, Yusnaini; Fatimah Nurjannati Iskandar (Ikatan Dosen Menulis, 2025)
This study aims to analyze the influence of consumer behavior on skincare product purchasing decisions through the Shopee platform among XYZ University students. This study was conducted using a quantitative explanatory research approach and data were collected through distributing questionnaires to 30 respondents selected using a purposive sampling technique. Data analysis was conducted using descriptive statistics, instrument testing, classical assumption testing, and simple linear regression to examine the influence of independent variables on the dependent variable. The results showed that consumer behavior has a positive and significant influence on skincare product purchasing decisions through Shopee. This is indicated by the coefficient of determination value of 82.9%, meaning consumer behavior is able to explain the contribution to purchasing decisions in the very strong category. Consumers consider product information, privacy security, platform reputation, trust, and purchase benefits as important factors driving purchasing decisions. Although some respondents are still neutral about the risks, overall consumer perceptions of Shopee are quite positive. The results of this study confirm that understanding consumer behavior is crucial for improving skincare product marketing strategies on e-commerce platforms.